Siglec-7 represents a glyco-immune checkpoint for non-exhausted effector memory CD8+ T cells with high functional and metabolic capacities - Haas, Quentin; Markov, Nikita; Muerner, Lukas; Rubino, Viviana; Benjak, Andrej; Haubitz, Monika; Baerlocher, Gabriela M.; Ng, Charlotte K. Y.; Münz, Christian; Riether, Carsten; Ochsenbein, Adrian F.; Simon, Hans-Uwe; et al. (Frontiers in Immunology, 2022)
While inhibitory Siglec receptors are known to regulate myeloid cells, less is known about their expression and function in lymphocyte subsets. Here we identified Siglec-7 as a glyco-immune checkpoint expressed on non-exhausted effector memory CD8+ T cells that exhibit high functional and metabolic capacities. Seahorse analysis revealed higher basal respiration and glycolysis levels of Siglec-7+ CD8+ T cells in steady state, and particularly upon activation. Siglec-7 polarization into the T cell immune synapse was dependent on sialoglycan interactions in trans and prevented actin polarization and effective T cell responses. Siglec-7 ligands were found to be expressed on both leukemic stem cells and acute myeloid leukemia (AML) cells suggesting the occurrence of glyco-immune checkpoints for Siglec-7+ CD8+ T cells, which were found in patients’ peripheral blood and bone marrow. Our findings project Siglec-7 as a glyco-immune checkpoint and therapeutic target for T cell-driven disorders and cancer.